2007
DOI: 10.1038/sj.jhh.1002305
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension-attributed symptoms in routine clinical practice: a general practitioners-based study

Abstract: The objective of the present study was to determine the prevalence of symptoms generally attributed to hypertension and the relationship between symptoms and blood pressure categories. Routine office blood pressure measurement in the morning was obtained and morning symptoms were reported using a standardized questionnaire in a multicenter study from general practitioners in Germany. Dizziness and headaches were significantly (Po0.001) more prevalent in 2154 untreated hypertensives (19.6 and 17.0%) as compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…In the current study, 51% of participants reported headaches, dizziness, and vision changes as their principal hypertensive symptoms. Both the frequency and symptoms identified are consistent with the findings of studies done with Europeans (Middeke et al., ; San Pedro et al., ). Middeke et al () studied the hypertensive symptom frequency and type in nearly 55,000 general practice patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the current study, 51% of participants reported headaches, dizziness, and vision changes as their principal hypertensive symptoms. Both the frequency and symptoms identified are consistent with the findings of studies done with Europeans (Middeke et al., ; San Pedro et al., ). Middeke et al () studied the hypertensive symptom frequency and type in nearly 55,000 general practice patients.…”
Section: Discussionsupporting
confidence: 88%
“…Both the frequency and symptoms identified are consistent with the findings of studies done with Europeans (Middeke et al., ; San Pedro et al., ). Middeke et al () studied the hypertensive symptom frequency and type in nearly 55,000 general practice patients. More than 30% of the participants attributed headaches, dizziness, dyspnea, or angina to their HTN.…”
Section: Discussionsupporting
confidence: 88%
“…For example, hypertensive people often have hypertension-attributed symptoms such as headache and dizziness in the morning. 29 In the current study, however, the analyses with the early cardiovascular events excluded did not substantially change the associations of breakfast intake frequency with the risk of total CVD, total stroke, and cerebral hemorrhage.…”
Section: Discussionmentioning
confidence: 81%
“…For example, hypertensive people often have hypertension-attributed symptoms such as headache and dizziness in the morning. 29 In the current study, however, the analyses with the early cardiovascular events excluded did not substantially change the associations of breakfast intake frequency with the risk of total CVD, total stroke, and cerebral hemorrhage.In the current study, the frequency of breakfast intake was inversely associated with the prevalence of participants with body mass index ≥25 kg/m 2 , whereas it was positively associated with the prevalence of diabetes mellitus. Although these associations seem incompatible, our baseline survey might reflect that after breakfast skippers were diagnosed with diabetes mellitus, they might have changed their unhealthy lifestyle, leading to loss of body weight, and started to eat breakfast to take medicines for diabetes mellitus before the baseline survey.…”
mentioning
confidence: 81%
“…A literature search3134 was conducted to compile potentially relevant concepts for hypertension self-management regarding symptoms of hypertension and its treatment, clinical measurements, and examples of lifestyle habits. Additional concepts were derived from a Swedish national multicenter study 35.…”
Section: Resultsmentioning
confidence: 99%